Exploration of new bismuth and lead-based metal-organic frameworks featuring free o and n donors: Synthesis, structures and properties / Mesoun A. A. Al Nubi Al Sudani - Mesoun A. A. Al Nubi , Al Sudani (2021)
This work describes the syntheses, characterizations and the properties of two new metal organic frameworks (MOFs) based on bismuth and lead cations with two different ligand linkers: 2,3-pyrazine dicarboxylic acid (H2Pzdc) and benzene 1,3,5-tricarboxylic acid (H3BTC). Bi-Pzdc MOFs have been synthesized by employing simple dissolution-slow evaporation method using mixture of water/DMF with different stoichiometric molar ratios and recruiting imidazole (Im) or imidazolium iodide (ImZm) as modulator agents. Pb-BTC MOFs synthesis have been conducted by employing simple and optimized solution layering approach using different mixture of water/1,4-Dioxane; water/DMF; and water/MeOH using same stoichiometric molar ratios and adopting Aniline (Ani) or Im as auxiliary ligands. The physical and chemical features of these MOFs have been characterized by using optical microscope, UV light black box, Scanning Electron Microscope coupled with Energy Dispersive X-Ray Spectroscopy SEM/EDX, Single Crystal and Powder X-ray diffraction (SC-XRD and PXRD), Thermo-gravimetric Analysis (TGA), elemental analysis (CHN), solid state Nuclear Magnetic Resonance (SS-NMR), Fourier Transform Infrared Spectrometry (FTIR), Ultra Violet-Visible (UV-Vis) spectrophotometry (solid and liquid state), solid state photoluminescence (PL), BET surface area analysis and proton conductivity measurements. SCXRD and PXRD measurements reveal that the new, water stable Bi-MOFs: (compounds 1 to 12), which all exhibit same structure; Bi(Pzdc)(HPzdc)(H2O); (H2pzdc= C6H3N2O4), crystallize in P21/n space group (a =14.1738(7) Å, b =21.682(1) Å, c =14.7988(8) Å,  =109.2103(8)°) and built from 2D slabs interlinked by Pzdc ligands into 3D MOF with 10.5 Å× 8.9 Å aperture size. A presence of hydrogen-bonded along the crystallographic c-direction, within the 2D slabs, possibly lead to the observed proton conductivity. Interestingly, its visible and photoluminescence colors depend on water content. Three new, closely resembled Pb-based organic frameworks are also reported in here along with their structural characterizations, photoluminescence, and dyes adsorption properties. Their SCXRD and PXRD measurements confirmed that Compounds 13 and 14 offered same formula, Pb(HBTC)(1,4-dioxane)0.5, and crystallize in the C2/c space group (a =17.239(2) Å, b =7.0225(8) Å, c =19.911(2) Å,  =104.74(1)); Compounds 15 and 17 display same formula as well, Pb2(HBTC)2(H2O)5, and crystallize in the P-1 space group (a = 7.3989(4) Å, b =8.2196(4) Å, c =10.1437(5) Å, α =94.336(4)°,  =104.943(4), γ =108.270(3)°); while Compound 18 with the formula, Pb(HBTC)(DMF), crystallizes in the P21/n space group (a = 10.5004 (3) Å, b = 7.1398 (3) Å, c = 17.1285 (5) Å,  =102.160(2)); (H3BTC= C9H6O6). All three lead compounds are built from slightly different 1D structures interconnected into 3D MOFs by BTC ligands forming different pore sizes which are governed by the solvent used during synthesis. Among them, only compound 17 showcases an interesting, near white-light emission, single-component phosphor with CIE coordinate of (0.33, 0.36), while compound 14 adsorbs methylene blue and methyl red dyes.